Regression of atherosclerotic lesions by high density lipoprotein plasma fraction in the cholesterol-fed rabbit. - Badimon, J J (1990)
The effects of homologous plasma HDL and VHDL fractions on established atherosclerotic lesions were studied in cholesterol-fed rabbits. Atherosclerosis was induced by feeding the animals a 0.5% cholesterol-rich diet for 60 d (group 1). Another group of animals were maintained on the same diet for 90 d (group 2). A third group was also fed the same diet for 90 d but received 50 mg HDL-VHDL protein per wk (isolated from normolipemic rabbit plasma) during the last 30 d (group 3). Aortic atherosclerotic involvement at the completion of the study was 34 +/- 4% in group 1, 38.8 +/- 5% in group 2, and 17.8 +/- 4% in group 3 (P less than 0.005). Aortic lipid deposition was also significantly reduced in group 3 compared with group 1 (studied at only 60 d) and group 2. This is the first in vivo, prospective evidence of the antiatherogenic effect of HDL-VHDL against preexisting atherosclerosis. Our results showed that HDL plasma fractions were able to induce regression of established aortic fatty streaks and lipid deposits. Our results suggest that it may be possible not only to inhibit progression but even to reduce established atherosclerotic lesions by HDL administration.